2016
DOI: 10.1021/jacs.6b06645
|View full text |Cite
|
Sign up to set email alerts
|

2-Aryl-5-carboxytetrazole as a New Photoaffinity Label for Drug Target Identification

Abstract: Photoaffinity labels are powerful tools for dissecting ligand–protein interactions, and they have a broad utility in medicinal chemistry and drug discovery. Traditional photoaffinity labels work through nonspecific C–H/X–H bond insertion reactions with the protein of interest by the highly reactive photogenerated intermediate. Herein, we report a new photoaffinity label, 2-aryl-5-carboxytetrazole (ACT), that interacts with the target protein via a unique mechanism in which the photogenerated carboxynitrile imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 29 publications
8
123
0
Order By: Relevance
“…[18] This crosslinking pattern is consistent with the results previously reported by us and others. [9,12] Docking experiments revealed that the distance between the tetrazole in Tz6 and Asp 110 was around 7.7 ,w hich is ar easonable distance for successful photo-crosslinking. Finally,w ee valuated the photo-crosslinking efficiency of Tz6 with recombinant annexin A2 by pull-down/WB,w hich appeared to be very high (Supporting Information, Figure S7).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[18] This crosslinking pattern is consistent with the results previously reported by us and others. [9,12] Docking experiments revealed that the distance between the tetrazole in Tz6 and Asp 110 was around 7.7 ,w hich is ar easonable distance for successful photo-crosslinking. Finally,w ee valuated the photo-crosslinking efficiency of Tz6 with recombinant annexin A2 by pull-down/WB,w hich appeared to be very high (Supporting Information, Figure S7).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[11] Our findings were further confirmed by afollowup work from Linsgroup,which showed 2-aryl-5-carboxytetrazole (ACT) can serve as an excellent photo-crosslinker in AfBP studies. [12] Recently,C ravatt et al reported that phenotypic screening and target identification can be integrated by using affinity-based probe compound libraries,s oa sto accelerate the mechanistic characterization of screening hits.…”
mentioning
confidence: 99%
“…However, its photogenerated intermediates show extremely short half‐lives, resulting in low target capturing yields, which is unfavorable toward the capturing of trace amount proteins in a single cell. [ 9 ] In addition, BP derived diradical intermediates are prone to react with proximal XH bonds (XC, N, O, or S), resulting in background autofluorecence, [ 10 ] which may obscure target signals in fluorescent analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of photoaffinity labeling (PAL) was originally introduced by Frank Westheimer in the early 1960s, 1 and since then it has gradually emerged as a powerful tool for the identication and localization of targets and corresponding interaction sites in complicated biological systems, 2 especially in some cases such as low-abundance proteins and low-affinity interactions that fail to survive disruptive washing steps. 3,4 Four common types of photoreactive group are used in PAL, namely, aryl azides (AZs), benzophenones (BPs), diazirines (DAs) 5,6 (New) and 2-aryl-5-carboxytetrazoles (ACTs), 7,8 which are classied in accordance with their photochemically generated reactive species, namely, nitrenes, diradicals, carbenes and carboxy-nitrile imines. In addition, some photoreactive components of natural molecules that can undergo photolysis to form highly reactive intermediates, such as steroid enones (e.g., pyrones and pyrimidones 9 ), various aryl chlorides, and several thioethers, have been utilized as probes to avoid complications associated with fully synthetic probes.…”
Section: Introductionmentioning
confidence: 99%